Nanoparticle conjugation of ginsenoside Rh2 enhanced antitumor efficacy on hepatocellular carcinoma - Fengkai Sun; Jinkun Liu; Shuai Gao; Mingchen Zhang; Xiaoyan Sun; Yanan Tian; Shengchun Wang (Scientific Reports)
Abstract Ginsenoside Rh2 (Rh2) is one of the main bioactive ginsenosides that act as a natural antitumor drug. However, the clinical application of Rh2 is limited by its low solubility in water. In this study, a novel ginsenoside Rh2 pH-sensitive liposome was constructed for targeted liver cancer therapy. Rh2 nanoparticles (NPs) exhibited an acid responsive mode, where cumulative release increased with the decrease in pH value. Rh2 and Rh2 NPs showed a dose-dependent inhibitory effect on Huh7 and MHCC97H cells. Rh2 and Rh2 NPs significantly inhibited tumor cell proliferation, migration, invasion and epithelial-mesenchymal transition, and promoted cell apoptosis and immunogenic cell death. Moreover, compared to Rh2 monomers, the Rh2 NPs exhibited improved antitumor effects in vitro. In vivo antitumor efficacy studies indicated that the Rh2 and Rh2 NPs significantly inhibited tumor growth, thereby decreasing tumor volume and weight at the end of the experiment compared with that in the control mice. Furthermore, Rh2 NPs had a more significant inhibitory effect on tumor growth compared with Rh2 monomers. Rh2 NPs might serve as a novel drug delivery system to enhance the antitumor potentials of Rh2 for effective liver cancer therapy.